METODE ONLINE TRADING DENGAN RELITRADE SEBAGAI LITERASI DALAM PENGEMBANGAN PEMBELAJARAN MATA KULIAH PASAR MODAL - Tine Badriatin (Unitri Press, 2019)
This research aims to determine the effect of online trading methods using relitrade as literacy for the development of capital market courses in the Financial and Banking Study Program at the Faculty of Economics, Siliwangi University, Tasikmalaya. This study uses a survey method with the fifth semester student population in the Finance and Banking Study Program. sampling based on specific objectives, namely selected respondents who have become stock investors and conduct online trading using relitrade so as to obtain 26 people. Data collection using a questionnaire with a Technology Acceptance Model (TAM) approach which includes 5 aspects, namely: perceived ease of use, perceived usefulness, attitudes towards technology use, behavioral interest in using technology, and actual use of technology. The results showed that the aspect of usability has the greatest value that is 96% which shows that the use of online trading systems is very effective in learning literacy and can encourage and motivate students in using technology to facilitate learning and trading about the capital market.